Dysphemism in the Comments Column of the @democrazymedia News Account on Application X - Fikriyyah Atikah; Hermandra; Charlina (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze the forms and functions of dysphemism in the comment section of the @democrazymedia news account on the X app. The study was conducted on the X social media platform, collecting data from the account’s comment section during the period from November to December 2025. The data in this study consists of 20 utterances containing dysphemism. The research instrument used was the researcher themselves, employing a read-and-record technique for data collection. Data analysis utilized a qualitative descriptive method with a semantic approach to identify the forms and functions of dysphemism. The results of the study indicate that there are 15 forms of dysphemism, namely figurative expressions, metaphors, re-modeling, circumlocution, clipping, ellipsis, abbreviations, acronyms, one word replacing another, general to specific, part for the whole, hyperbole, meaning beyond the statement, jargon, and colloquialisms. In terms of function, dysphemisms are used to convey things considered taboo or indecent, describe situations negatively, express criticism, belittle and mock, as well as exaggerate situations and hurl insults. The most dominant function is as a means of belittling and mocking.